Avaliação de acidentes de trabalho no setor elétrico: estudo de caso no nordeste do Brasil - Almeida, Ana Lúcia Menezes de (2012)
The occurrence of occupational accidents is still a significant problem that affects organizations, workers and governments around the world. Risk factors associated with working in the electricity sector are many, going through of electrical origin, fall, transportation, occupational and other, so that makes it possible to map these risks prevention. In the case of this sector, although there was a significant decrease in the number of accidents, the company studied has a frequency rate and severity above the industry average. Thus this research studied the records of accidents at work involving electrical industry professionals. The method used was based on the literature review on the topic, and a documentary analysis, using materials provided by the company. As a result, it was observed that most accidents occur, in the electricity sector, with men 51-60 years old, with technical industrial and maintenance of transmission lines professionals. Most accidents are falls, being classified as typical, resulting in temporary disability. Occur within the company and mostly in the East System. By identifying the characteristics of the accidents we obtain information on which to base preventive measures among professionals of the sector.